Knowledge management in education in response to dominant thinking trends in school - Gutierrez Vargas, Giovanni (Revista Complutense de Educación, 2018)
A study is presented that recognizes how the value conferred to knowledge in education is one of the strategies with which it confronts the tendencies of the thought whose purpose is to project a school based on the operational competences, the efficiency and the service of the productive rationality companies. Through the incursion into literature developed in the field of administration and business, the work exposes the way in which the management of knowledge, produced in the school environment, is seen as a way of liberating the totalizing and unifying effect of knowledge scientific and technological that have misplaced the triad, made up of understanding, critical thinking and wisdom, which was the essence of educational activity until the emergence of post-industrial society. Finally,the article proposes basic principles that allow the educational knowledge to affect the thinking-act of the school institution.
Keywords: knowledge; school; cultural patterm; education system; society